Listeria monocytogenes Methods and Protocols - Jordan, Kieran.; Jordan, Kieran.; Fox, Edward M.; Fox, Edward M.; Wagner, Martin.; Wagner, Martin. (Methods in Molecular Biology, 2014)
Listeria monocytogenes is still a major threat to public health. A new book in the Methods in Molecular Biology series, Listeria monocytogenes: Methods and Protocols addresses its titular pathogen with protocols and methodologies used in research to gain a better understanding of Listeria at a molecular level. The topics covered include sampling in order to isolate Listeria, methods for their identification and characterization, methods for gene manipulation, and, finally, methods for control of the organism. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective subjects, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Vital and authoritative, Listeria monocytogenes: Methods and Protocols aims to contribute to the harmonization of the methods used in the field and will therefore benefit all those interested in Listeria research.